Various Parameters Affecting To the Dried Salted Snakehead Fish Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Fish is highly perishable, and is spoiled rapidly if improperly handled. Salted dried, one of the techniques for preserving fish has been practiced for long period and it is an alternative to lowering the water activity of ﬂesh fish. Snakehead fish (Channa striata) is a potential freshwater fish species and has become an important commodity in health food industry due to its abundant albumin content. The snakehead fish has commercial value due to its health benefit. It is a good source of medicinal food because it contains high level of amino acids and fatty acids. Therefore we conducted several experiments to identify the effect of salt soaking time, salt soaking concentration, dry temperature and stability of the dried snakehead fish filler by prerservation time. Our results showed that the best quality of the dried snakehead fish fillet could be obtained if the dried snakehead fish fillet treated with 1.0% salt in 1.5 hours and drying at 60oC to 20% moisture content. This application could preserve the dried snakehead fish fillet for 12 months in PA bag without any deterioration. Through this investigation, the added value of snakehead fish could be improved in domestic consumption.Keywords: Snakehead fish, Fillet, Salinity, Drying, Soaking, Preservation